Comparison of nonoperative versus operative management in pediatric gustilo-anderson type I open tibia fractures. Issue 2 (February 2023) - Padgett, Anthony M.; Torrez, Timothy W.; Kothari, Ezan A.; Conklin, Michael J.; Williams, Kevin A.; Gilbert, Shawn R.; Ashley, Philip
Abstract: Background: Recent studies suggest pediatric Gustilo-Anderson type I fractures, especially of the upper extremity, may be adequately treated without formal operative debridement, though few tibial fractures have been included in these studies. The purpose of this study is to provide initial data suggesting whether Gustilo-Anderson type I tibia fractures may be safely treated nonoperatively. Methods: Institutional retrospective review was performed for children with type I tibial fractures managed with and without operative debridement from 1999 through 2020. Incomplete follow-up, polytrauma, and delayed diagnosis of greater than 12 h since the time of injury were criteria for exclusion. Data including age, sex, mechanism of injury, management, time-to-antibiotic administration, and complications were recorded. Results: Thirty-three patients met inclusion criteria and were followed to union. Average age was 9.9 ± 3.7 years. All patients were evaluated in the emergency department and received intravenous antibiotics within 8 h of presentation. Median time-to-antibiotics was 2 h. All patients received cefazolin except one who received clindamycin at an outside hospital and subsequent cephalexin. Three patients (8.8%) received augmentation with gentamicin. Twenty-one patients (63.6%) underwent operative irrigation and debridement (I&D), and of those, sixteen underwent surgical fixation of their fracture. Twelve (36.4%) patients had bedside I&D with saline under conscious sedation, with one requiring subsequent operative I&D and intramedullary nailing. Three infections (14.3%) occurred in the operative group and none in the nonoperative group. Complications among the nonoperative patients include delayed union (8.3%), angulation (8.3%), and refracture (8.3%). Complications among the operative patients include delayed union (9.5%), angulation (14.3%), and one patient experienced both (4.8%). Other operative group complications include leg-length discrepancy (4.8%), heterotopic ossification (4.8%), and symptomatic hardware (4.8%). Conclusion: No infections were observed in a small group of children with type I tibia fractures treated with bedside debridement and antibiotics, and similar non-infectious complication rates were observed relative to operative debridement. This study provides initial data that suggests nonoperative management of type I tibial fractures may be safe and supports the development of larger studies. Highlights: The results of this study provide initial data that type I open tibial fractures in pediatric patients may be effectively managed without formal operative irrigation and debridement. Concordant with previous studies, minimizing the time to antibiotic treatment is of upmost importance in the management of open fractures. There remains a need for well-designed future studies to delineate the indications for operative versus nonoperative management of type I open fractures.